1998
DOI: 10.1046/j.1365-2885.1998.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the haemodynamic effects of propofol and isoflurane in pregnant ewes

Abstract: The purpose of this study was to compare the effects of inhaled isoflurane and a constant infusion of propofol on maternal haemodynamics and uterine arterial and umbilical venous flows in pregnant ewes. Late term pregnant ewes (n = 5) were randomly assigned to receive either inhaled isoflurane or an intravenous infusion of propofol for 1 h, each on separate occasions. Maternal systemic arterial, right atrial and pulmonary arterial blood pressures, cardiac index, systemic vascular resistance index, stroke volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…Another report suggested that the maternal hemodynamics were less depressed with a continuous propofol infusion than with inhalation of isoflurane [11]. Consistent with these data, there was no finding indicating the hemodynamic suppression in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another report suggested that the maternal hemodynamics were less depressed with a continuous propofol infusion than with inhalation of isoflurane [11]. Consistent with these data, there was no finding indicating the hemodynamic suppression in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the rapid emergence and disappearance of the anesthetic effect depending on a rapid redistribution of the drug from the central nervous system [18,28], propofol can also be injected either continuously or repeatedly to maintain general anesthesia instead of the use of volatile anesthetics [21,30]. Some reports on propofol in pregnant animal, have shown that continuous propofol anesthesia would not adversely affect maternal or fetal heart rate and blood pressure [2,11], cause less decrease in uterine blood flow [2,11], or suppress spontaneous uterine contraction [17]. Except for its less analgesic action, propofol could be safer for pregnant animals as compared with the other induction agents.…”
mentioning
confidence: 99%
“…This can in part be explained as a compensatory change occurring in response to lower systemic blood pressures caused by the higher propofol (Goodchild & Serrao 1989) and isoflurane (Bernards et al. 1997; Gaynor et al. 1998) doses required in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…1985) caused by the higher MED dose and, or the lower propofol and isoflurane requirements (Goodchild & Serrao 1989); (Bernards et al. 1997; Gaynor et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Embora tenha ocorrido esta diminuição de aporte sanguíneo, houve associadamente um decréscimo do requerimento de oxigênio, não havendo comprometimento de órgãos vitais. Quando o isoflurano foi comparado ao propofol, um anestésico não volátil, em ovinos, verificou-se que o propofol em infusão contínua causa uma menor depressão cardiovascular em ovelhas gestantes, porém não há diferenças entre os dois fármacos no que concerne ao fluxo sanguíneo nas artérias umbilicais (5) . Além da estabilidade cardiopulmonar, a anestesia geral inalatória em ovinos é interessante por proporcionar uma recuperação anestésica rápida, diminuindo o risco de regurgitação, mas o uso de agentes injetáveis associados pode anular esta vantagem (6) .…”
Section: Introductionunclassified